The role of top management team human capital in venture capital markets: Evidence from first-time funds - Zarutskie, Rebecca (Journal of Business Venturing, 2010)
This paper examines whether the human capital of first-time venture capital fund management teams can predict fund performance and finds that it can. I find that fund management teams with more task-specific human capital, as measured by more managers having past experience as venture capitalists and by more managers having past experience as executives at start-up companies, manage funds with greater fractions of portfolio company exits. I also find that fund management teams with more industry-specific human capital in strategy and management consulting and, to a lesser extent, engineering and non-venture finance manage funds with greater fractions of portfolio company exits. Perhaps counter-intuitively, I find that fund management teams that have more general human capital in business administration, as measured by more managers having MBAs, manage funds with lower fractions of portfolio company exits. Overall, measures of task- and industry-specific human capital are stronger predictors of fund performance than are measures of general human capital.